fNIRS detects temporal lobe response to affective touch - Bennett, Randi H. (Oxford University Press, 2014)
Touch plays a crucial role in social–emotional development. Slow, gentle touch applied to hairy skin is processed by C-tactile (CT) nerve fibers. Furthermore, ‘social brain’ regions, such as the posterior superior temporal sulcus (pSTS) have been shown to process CT-targeted touch. Research on the development of these neural mechanisms is scant, yet such knowledge may inform our understanding of the critical role of touch in development and its dysfunction in disorders involving sensory issues, such as autism. The aim of this study was to validate the ability of functional near-infrared spectroscopy (fNIRS), an imaging technique well-suited for use with infants, to measure temporal lobe responses to CT-targeted touch. Healthy adults received brushing to the right forearm (CT) and palm (non-CT) separately, in a block design procedure. We found significant activation in right pSTS and dorsolateral prefrontal cortex to arm > palm touch. In addition, individual differences in autistic traits were related to the magnitude of peak activation within pSTS. These findings demonstrate that fNIRS can detect brain responses to CT-targeted touch and lay the foundation for future work with infant populations that will characterize the development of brain mechanisms for processing CT-targeted touch in typical and atypical populations.